Implementasi Media Pohon Literasi untuk Meningkatkan Literasi Sains Murid pada Mata Pelajaran IPA - Lusiana Dewi; Sri Jumini; Nugroho Prasetya Adi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2022)
The low scientific literacy in Indonesia shows that students don’t understand the concepts, processes, and applications of science in life. This can be overcome by the application of teaching aids in learning activities, by literacy tree. The research was conducted with the aim of knowing an increase in students' scientific literacy by applying the media literacy tree to science subjects. This research is an experimental study with a true experimental design using a pretest-posttest control group design. The sample selection in this study used a cluster random sampling technique, taking a sample of 64 students who were divided into the experimental group and the control group. The results of the study indicate that the average N-Gain test in the experimental is 0.6 and the control is 0.4. The results of the statistical test tcount > ttable, means a significant difference between the control and experimental groups. The study concluded the scientific literacy of the experimental by applying the literacy tree media was superior to the scientific literacy of the control by applying conventional media so that the application of the literacy tree media into learning activities could improve students' scientific literacy in science lessons.